2012
DOI: 10.1074/jbc.m112.367367
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-activated Receptor α (PPARα) Suppresses Hypoxia-inducible Factor-1α (HIF-1α) Signaling in Cancer Cells

Abstract: Background:The mechanisms of PPAR␣-mediated inhibition of tumor growth and angiogenesis remain unknown. Results: Activation of PPAR␣ suppresses hypoxia-induced HIF-1␣ signaling via promoting HIF-1␣ degradation and diminishes hypoxia-induced VEGF secretion from cancer cells and tube formation by endothelial cells. Conclusion: Activation of PPAR␣ suppresses the HIF-1␣ signaling pathway in cancer cells. Significance: The results support the development of PPAR␣ agonists as anticancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 45 publications
2
59
0
1
Order By: Relevance
“…42,58 In turn, HIF-1a enhances transcription of Nox 4. 32 Our results in the OIR retina are consistent with previous findings, suggesting that PPARa likely decreases hypoxia-induced Nox 4 upregulation by accelerating HIF-1a degradation.…”
Section: Discussionmentioning
confidence: 99%
“…42,58 In turn, HIF-1a enhances transcription of Nox 4. 32 Our results in the OIR retina are consistent with previous findings, suggesting that PPARa likely decreases hypoxia-induced Nox 4 upregulation by accelerating HIF-1a degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that fenofibrate can be used to inhibit the growth of several cancer lines, such as colon, breast, endometrial, and skin cancers [7][8][9][10]. Fenofibrate can suppress hypoxiainduced HIF-1α signaling via promoting HIF-1α degradation and diminishing hypoxia-induced VEGF secretion from MCF-7 cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then transfected with the luciferase reporter constructs including the pGL3/4.5-HO-1 and its mutants, the HO-1-3'-UTR and GAPDH-3'-UTR using the Fugene HD transfection reagent (Roche, Mannheim, Germany) as previously described [6]. The next day, cells were lifted and plated into 24-well plates at a density of 2×10 5 per well.…”
Section: Methodsmentioning
confidence: 99%
“…48 hours after transfection, cells were treated with various reagents at indicated concentrations and durations. Cell lysates were prepared and luciferase activity was assayed using the Dual-Luciferase Reporter kit, as previously described [6]. The firefly luciferase activity was normalized to the amount of protein present in each sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation